1995
DOI: 10.2977/prims/1195164793
|View full text |Cite
|
Sign up to set email alerts
|

General Existence Theorems for Orthonormal Wavelets, an Abstract Approach

Abstract: Methods from noncommutative harmonic analysis are used to develop an abstract theory of orthonormal wavelets. The relationship between the existence of an orthonormal wavelet and the existence of a multi-resolution is clarified, and four theorems guaranteeing the existence of wavelets are proved. As a special case of the fourth theorem, a generalization of known results on the existence of smooth wavelets having compact support is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 5 publications
0
57
0
1
Order By: Relevance
“…GMRAs were introduced in [4], and have since been studied in [5] and [3]; other authors had previously observed that much of the theory still works when we use Γ in place of the classical translation group Z n (see [1] and [9], for example).…”
Section: Multiplicity Functions and The Main Theoremmentioning
confidence: 99%
“…GMRAs were introduced in [4], and have since been studied in [5] and [3]; other authors had previously observed that much of the theory still works when we use Γ in place of the classical translation group Z n (see [1] and [9], for example).…”
Section: Multiplicity Functions and The Main Theoremmentioning
confidence: 99%
“…It does not address the problem of constructing smooth refinable distributions, nor does it address the problem of constructing wavelet bases. However, we note that Bagget, Carey, Moran, and Ohring showed [1], using properties of von Neumann algebras [19], [9], that the existence of stable refinable functions in L 2 (G) implies the existence of orthonormal wavelet bases for L 2 (G). .…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…, ψ L ; and one can consider an orthonormal basis for a closed subspace of L 2 (R). There have also been several publications of wavelets in higher dimensions, cf [1,2,3,5,10,12,13,14,21,22,23] to name few. One of the differences in higher dimensions is that we now have many more choices in the sets of dilations and translations.…”
Section: Introductionmentioning
confidence: 99%